Motivation for self-study among medical university students - Sithija Dilshan, Jayakodi Waththage; Karnialiuk, Dzmitry; Lakotka, Tatsiana; Khan, Fawzer Khan Akil Ahamed (International Journal of Research in Medical Sciences, 2024)
Background: Motivation is a key driver of academic success, especially in rigorous disciplines like medicine. Recognizing what motivates students to engage in self-study can provide essential insights for enhancing educational practices. Methods: The study employed the academic motivation scale (AMS). The survey was administered online through Google forms, targeting 4th-year students from both the domestic faculty of medicine and the faculty of foreign students. The AMS assesses several components of internal motivation (such as the desire to gain knowledge) and external motivation (such as motivation due to external rewards or pressures). A comparative analysis was conducted to highlight differences in motivation between the two student groups. Results: The findings demonstrated, that foreign students consistently exhibited higher levels of internal motivation, including a greater desire to understand medical content and achieve academic success. They also scored higher on most external motivational factors, such as motivation stemming from rewards or recognition. These results indicate that foreign students tend to be more academically motivated than domestic students at Grodno State Medical University. Conclusions: The study underscores the critical role of both internal and external motivation in promoting academic performance, especially in medical education. The greater motivation observed among foreign students suggests that cultural, environmental, or personal factors might contribute to their stronger drive for self-study. Future research could investigate these factors more deeply and develop targeted approaches to enhance motivation among all students. Implementing strategies to improve intrinsic motivation among domestic students could help reduce the observed disparity.